2007
DOI: 10.1021/es072014b
|View full text |Cite
|
Sign up to set email alerts
|

“Phytoscreening”: The Use of Trees for Discovering Subsurface Contamination by VOCs

Abstract: We tested the possibility of using tree cores to detect unknown subsurface contamination by chlorinated volatile organic compounds (Cl-VOCs) and petroleum hydrocarbons, a method we term "phytoscreening". The scope and limitations of the method include the following: (i) a number of widespread Cl-VOC contaminants are readily found in tree cores, although those with very high vapor pressures or low boiling points may be absent; (ii) volatile petroleum hydrocarbons were notwell-expressed in tree cores; (iii) tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 25 publications
2
76
0
Order By: Relevance
“…Today, phytoscreening of soil and groundwater has become a scientifically validated and recognized method (Sorek et al 2008; Gopalakrishnan et al 2007) and has frequently been used to investigate plumes of chlorinated solvents, such as tetrachloroethene, trichloroethene, and cis-1,2-dichloroethene (Sorek et al 2008; Larsen et al 2008). The principle underlying the method is that contaminants are taken up by roots and translocated upwards to the stem.…”
Section: Background Aim and Scopementioning
confidence: 99%
“…Today, phytoscreening of soil and groundwater has become a scientifically validated and recognized method (Sorek et al 2008; Gopalakrishnan et al 2007) and has frequently been used to investigate plumes of chlorinated solvents, such as tetrachloroethene, trichloroethene, and cis-1,2-dichloroethene (Sorek et al 2008; Larsen et al 2008). The principle underlying the method is that contaminants are taken up by roots and translocated upwards to the stem.…”
Section: Background Aim and Scopementioning
confidence: 99%
“…Translocation of metals from roots to shoots has been shown to vary in the presence of biochar in some cases (Rees et al 2015), however, investigations of the precise localization of pollutants in the different plant tissues have seldom been made. For some volatile organic pollutants, release of pollutants accumulated by plants may occur via evapotranspiration or outward diffusion from above-ground biomass (Sorek et al 2007). Biochar might affect this process through adsorbing the compounds in the root zone, thereby reducing phytoavailability, or by affecting plant metabolic processes, but few related investigations have been made so far.…”
Section: Soil Remediationmentioning
confidence: 99%
“…Researchers also have shown that the tree-core technique for oaks and cypress trees has been a useful indicator of the presence of chlorinated solvents from groundwater contamination (Doucette et al 1998;Vroblesky et al 1999a) and in a variety of hardwood and softwood species Schumacher et al 2004;Sorek et al 2008), and petroleum hydrocarbons such as benzene, toluene, trimethylbenzene isomers, and methyl tert-butyl ether (MTBE) in oak trees (Landmeyer et al 2000;Arnold et al 2007). In those studies, cores of trunk material were collected using standard increment-borer techniques; core material was placed in glass vials that were capped with gas-tight seals, and compounds in the headspace were then identified using a field gas chromatograph with a photoionization detector (Vroblesky et al 1999a).…”
Section: Plant Tissue Samplesmentioning
confidence: 99%